Short-term outcomes of near-infrared imaging using indocyanine green in laparoscopic lateral pelvic lymph node dissection for middle-lower rectal cancer: A propensity score-matched cohort analysis - Jin-Yu Dai; Zhi-Jun Han; Jing-Dong Wang; Bao-Shuang Liu; Jian-Yu Liu; Yan-Cheng Wang (Frontiers in Medicine, 2022)
Laparoscopic lateral pelvic lymph node dissection (LPND) is limited by complex neurovascular bundles in the narrow pelvic sidewall and various post-operative complications. Indocyanine green (ICG) has been applied to increase the number of harvested lymph nodes and reduce the injury of irrelevant vessels in patients with rectal cancer. However, few studies on the recurrence rate of ICG fluorescence imaging-guided laparoscopic LPND were reported. This retrospective study enrolled 50 middle- low rectal cancer patients who were treated by LPND. After propensity score matching, 20 patients were matched in each of the indocyanine green (ICG) guided imaging group (ICG group) and non-ICG guided imaging group (non-ICG group). The average follow-up time was 13.5 months (12–15 months). Our results showed that the total number of harvested lymph nodes in the ICG group was significantly higher than that in the non-ICG group (P < 0.05), and intraoperative blood loss and post-operative hospital stay times in the ICG group were less than those in the non-ICG group (P < 0.05). After 12 months of follow-up, no residual lymph node and local tumor recurrence were found for patients in the ICG group. Four patients in the non-ICG group detected residual lymph nodes at the 3-month visit. Our findings highlighted the importance of ICG fluorescence-guided imaging in LPND because it has unique advantages in improving the number of lymph node dissections, surgical accuracy, and decreasing the residual lymph nodes and local tumor recurrence. In addition, ICG fluorescence guidance technology can effectively shorten the operation time, and it is simple to operate, which is worth popularizing.